Too Fast, too Straight, too Weird: Non-Reactive Indicators for Meaningless Data in Internet Surveys - Leiner, Dominik J (Survey research methods, 2019)
Practitioners use various indicators to screen for meaningless, careless, or fraudulent responses in Internet surveys. This study employs an experimental-like design to empirically test the ability of non-reactive indicators to identify records with low data quality. Findings suggest that careless responses are most reliably identified by questionnaire completion time, but the tested indicators do not allow for detecting intended faking. The article introduces various indicators, their benefits and drawbacks, proposes a completion speed index for common application in data cleaning, and discusses whether to remove meaningless records at all.